2013
DOI: 10.1152/jn.00065.2013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of postural threat on spinal stretch reflexes: evidence for increased muscle spindle sensitivity?

Abstract: Standing balance is often threatened in everyday life. These threats typically involve scenarios in which either the likelihood or the consequence of falling is higher than normal. When cats are placed in these scenarios they respond by increasing the sensitivity of muscle spindles imbedded in the leg muscles, presumably to increase balance-relevant afferent information available to the nervous system. At present, it is unknown whether humans also respond to such postural threats by altering muscle spindle sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 55 publications
3
81
0
Order By: Relevance
“…After each block, participants completed questionnaires (in approximately 3 min) to assess their perceived anxiety (sum of 10-item, 9-point Likert scale; max = 90), fear (0% = not fearful, 100% = extremely fearful), and stability (0% = not stable, 100% = completely stable) [14]. In the High Condition only, subjects were also asked to estimate the height at which they stood, in order to calculate a ratio of overestimation (RoO, estimated height/actual virtual height of 3.2 m) which is known to be increased with fear [4,15]. All questionnaires were projected in the virtual environment, and verbal responses to each question were manually recorded.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…After each block, participants completed questionnaires (in approximately 3 min) to assess their perceived anxiety (sum of 10-item, 9-point Likert scale; max = 90), fear (0% = not fearful, 100% = extremely fearful), and stability (0% = not stable, 100% = completely stable) [14]. In the High Condition only, subjects were also asked to estimate the height at which they stood, in order to calculate a ratio of overestimation (RoO, estimated height/actual virtual height of 3.2 m) which is known to be increased with fear [4,15]. All questionnaires were projected in the virtual environment, and verbal responses to each question were manually recorded.…”
Section: Data Collectionmentioning
confidence: 99%
“…Under threatening conditions, the amplitude and frequency of sway during static balance is altered, and may be associated with concomitant changes in tonic muscle activity of lower leg muscles [3], increased stiffness [3], and increased proprioceptive and vestibular reflex gains [4,5]. The effects of threat on dynamic balance reactions are less clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fear of falling is one of the factors of "postural threat, " which has been reported to increase the excitability of the spinal stretch reflex [12]. Enhanced sympathetic and fusimotor drive during postural threat are thought to increase muscle spindle sensitivity [13]. Therefore, an unsteady gait on the ground may have led to spastic EMG activities through postural threat.…”
Section: Discussionmentioning
confidence: 99%
“…Standing on an elevated surface also induced increases in fear of falling, sympathetic arousal, and stress response (Cleworth et al 2012;Horslen et al 2014). More recent studies focused on the underlying mechanisms of this adaptive response and showed that postural threat is likely to induce changes in two of the sensory channels involved in postural control, proprioceptive (Davis et al 2011;Horslen et al 2013), and vestibular (Horslen et al 2014;Lim et al 2017).…”
Section: Introductionmentioning
confidence: 99%